The ‘lost’ islands of Cardigan Bay, Wales, UK: insights into the post-glacial evolution of some Celtic coasts of northwest Europe - Haslett, Simon K.; Willis, David (Atlantic Geoscience, 2022)
A 13th –14th-century map held in the Bodleian Library (the Gough Map and the oldest map of Great Britain) shows two ‘lost’ islands in Cardigan Bay offshore west Wales, United Kingdom. This study investigates historical sources, alongside geological and bathymetric evidence, and proposes a model of post-glacial coastal evolution that provides an explanation for the ‘lost’ islands and a hypothetical framework for future research: (1) during the Pleistocene, Irish Sea ice occupied the area from the north and west, and Welsh ice from the east, (2) a landscape of unconsolidated Pleistocene deposits developed seaward of a relict pre-Quaternary cliffline with a land surface up to ca. 30 m above present sea-level, (3) erosion proceeded along the lines of a template provided by a retreating shoreline affected by Holocene sea-level rise, shore-normal rivers, and surface run-off from the relict cliffline and interfluves, (4) dissection established islands occupying cores of the depositional landscape, and (5) continued down-wearing, marginal erosion and marine inundation(s) removed the two remaining islands by the 16th century. Literary evidence and folklore traditions provide support in that Cardigan Bay is associated with the ‘lost’ lowland of Cantre’r Gwaelod. The model offers potential for further understanding post-glacial evolution of similar lowlands along northwest European coastlines.